Construction of human MASP-2-CCP1/2SP, CCP2SP, SP plasmid DNA nanolipoplexes and the effects on tuberculosis in BCG-infected mice. (August 2017) - Gao, Qi; Dong, Xinfang; Luo, Yanping; Zhang, Guochao; Shan, Jinyu; Wang, Qian; He, Qi; Zhang, Lifeng; Wang, Jingqiu; Zhu, Bingdong; Ma, Xingming
Abstract: The lectin pathway, one of the complement cascade systems, provides the primary line of defense against invading pathogens. The serine protease of MASP-2 plays an essential role in complement activation of the lectin pathway. The C-terminal segment of MASP-2 is comprised of the CCP1-CCP2-SP domains, and is the crucial catalytic segment. However, what is the effect of CCP1-CCP2-SP domains in controlling chronic infection is unknown. In order to evaluate the potential impact of CCP1-CCP2-SP domains on tuberculosis, we constructed the human MASP-2 CCP1/2SP, CCP2SP and SP recombinant plasmids, and delivered these plasmids by DNA-DOTAP:cholesterol cationic nanolipoplexes to BCG-infected mice. After 21 days post DNA-DOTAP:chol nanolipoplexes application, we analyzed bacteria loads of pulmonary, pathology of granuloma, lymphocyte subpopulations. The C3a, C4a and MASP-2 levels in serum were measured with enzyme-linked immunosorbent assays. Compared to the control group that received GFP DNA-DOTAP:chol nanolipoplexes, MASP-2 CCP1/2SP DNA-DOTAP:chol nanolipoplexes treated group showed significantly enlarged pulmonary granulomas lesion (P < 0.05) and did not reduce bacteria loads in the lung tissue (P < 0.05). Furthermore, the levels of C3a in serum were decreased (P < 0.05), the number and percentage of PD1 + and Tim3 + cells subgroups were increased in BCG-infected mice after treated with MASP-2 CCP1/2SP DNA-DOTAP:chol nanolipoplexes (P < 0.05). But, there was no statistical difference in the serum C4a and MASP-2 level among DNA nanolipoplexes treated groups (P > 0.05). These findings provided experimental evidence that MASP-2 CCP1/2SP DNA nanolipoplexes shown the negative efficacy in controlling Mycobacterium tuberculosis infection, and displayed a potential role of down-regulating T-cell-mediated immunity in tuberculosis. Highlights: The human MASP-2-CCP1/2SP, CCP2SP and SP plasmid DNA-DOTAP:Chol cationic nanoliposomes were firstly successful constructed. A significantly enlarged of granulomas lesion and no reducing of bacteria loads in the lung tissue of MASP-2 CCP1/2SP DNA lipoplexes treated group. A marked increasing in the population of PD1 + and Tim3 + T cells and down-regulating T-cell-mediated immunity of MASP-2 CCP1/2SP DNA lipoplexes treated group.